2017
DOI: 10.2460/ajvr.78.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of terbinafine in little brown myotis (Myotis lucifugus) infected with Pseudogymnoascus destructans

Abstract: OBJECTIVE To determine the pharmacokinetics of terbinafine in little brown myotis (Myotis lucifugus) infected with Pseudogymnoascus destructans. ANIMALS 123 bats from a P destructans-infected hibernation site in Virginia. PROCEDURES 3 bats were euthanized and necropsied to confirm the presence of P destructans within the population. The remaining 120 bats were systematically assigned to 6 groups (20 bats/group). Bats in each of 3 groups received 6, 20, or 60 mg of terbinafine/kg, SC, once daily for 10 days. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…included both topical, oral and implanted treatments for hosts as well as attempts to reduce the environmental pathogen reservoir and delay transmission. Several treatments have now been tested in vitro, in vivo or in situ 133,135,[154][155][156][157][158] , including antifungal chemicals, volatile organic compounds, probiotic microbes, biopolymers and vaccines (reviewed elsewhere 153,155 ). Currently, only one probiotic treatment and a vaccine have been shown to reduce mortality in a single species, M. lucifugus 135,155 ; however, no treatment has been deployed on a landscape scale.…”
Section: Box 1 | Ecosystem Impacts Of White-nose Syndromementioning
confidence: 99%
“…included both topical, oral and implanted treatments for hosts as well as attempts to reduce the environmental pathogen reservoir and delay transmission. Several treatments have now been tested in vitro, in vivo or in situ 133,135,[154][155][156][157][158] , including antifungal chemicals, volatile organic compounds, probiotic microbes, biopolymers and vaccines (reviewed elsewhere 153,155 ). Currently, only one probiotic treatment and a vaccine have been shown to reduce mortality in a single species, M. lucifugus 135,155 ; however, no treatment has been deployed on a landscape scale.…”
Section: Box 1 | Ecosystem Impacts Of White-nose Syndromementioning
confidence: 99%
“…While non-lethal diagnostic tools offer the opportunity to follow the progression of skin pathology, prior experience with WNS pathology scores may be used to predict the outcome of infection in a diseased bat. With intensive research for treatment of WNS in North America [ 24 ], ability to predict patient prognosis becomes imperative. Lacking sufficient sample sizes for statistical model evaluation, case report experience might provide valuable information.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 15 years, extensive research has revealed much about the disease ecology of WNS, including the interactions between the pathogen, environments where bats hibernate, and the physiology of hibernating bats (see 12 for recent comprehensive review). Research efforts have also focused on testing potential management actions aimed to reduce transmission or spread, lower disease severity, or improve survival 15 18 . One of the challenging aspects of managing WNS is that the pathogen persists in the environment where bats hibernate, exposing bats to infection at the start of each hibernation season 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%